Effect of GA3 and IAA on Growth and Leaves Content of Volatile Oil in Sweet Basil ( Ocimum basilicum L.) - Al- Kaisi, W.A; Bashii, R.W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study was designed to invetigate the effect of two plant growth regulators (GA3 and IAA)on growth and leaves volatile oils of sweet basil .      The plants were treated with 200ppm concentration for each of the bove regulators after 2 monthes  of planting ,after 2weeks of the first treatment and after month of the first treatment .     The results showed an increase in plant height 25,35% ,number of large leaves 20,40% and percentage of volatile oils 200,100%respectively after one month of first treatment.